HLA-F displays highly divergent and frequent haplotype lineages associated with different mRNA expression levels - Buttura, Renato V. [UNESP] (2019)
HLA-F is one of the most conserved loci among the HLA gene family. The exact function of HLA-F is still under investigation. HLA-F might present tolerogenic features, participate in the stabilization of HLA molecules in open conformation, and also participate in the recycling of HLA molecules. Here we evaluate the variability and haplotype structure of the HLA-F distal promoter segment (from −1893 to −943) and how this segment is correlated with the coding region. Variability at the promoter segment was surveyed in 196 Brazilian samples using second-generation sequencing. The HLA-F promoter region presents two major haplotype lineages. Most of the variable sites are in perfect linkage and associated with a single promoter haplotype, here named F ∗ distal-C. This haplotype is associated with F ∗ 01:01:02 alleles, while alleles from the F ∗ 01:01:01 or F ∗ 01:03 groups present closely related promoter sequences. F ∗ distal-C is quite frequent in Brazil and in worldwide populations, with frequencies ranging from 8.41% at the Iberian Population in Spain to 34.34% in Vietnam. F ∗ distal-C is also present in Neanderthal and Denisovan samples. In silico analyses demonstrated that F ∗ distal-C presents a different transcription factor binding profile compared with other HLA-F promoters. Moreover, individuals carrying this haplotype present higher HLA-F mRNA expression levels. Functional studies are required to define the exact mechanism underlying this higher HLA-F mRNA expression level associated with F ∗ distal-C and F ∗ 01:01:02 alleles.